Integrative analysis of the disciplinary administrative process and the principle of efficiency (Research, Society and Development, 2021)
The administrative reform brought about by the Constitutional Amendment (EC) 19/98 positivity in the Brazilian legal system the principle of efficiency. Public managers must, since then, be guided by the primacy of legality, impersonality, morality, publicity and by an efficient administration. The Disciplinary Administrative Process (PAD) is central to the public administrator, because it is with this tool that he can make the disciplinary control of public servants, people who make the public service reach society. O work item or objective to verify from an integrative review how it is characterized by administrative efficiency not in the context of public administration, administrative process and the principle of efficiency applied to the disciplinary administrative process, taking into consideration articles with Qualis Capes A1 to B4 published no period from 2010 to 2020. The method of integrative literature review was used, with a search for studies related to the theme, on platforms with indexed journals, with publication date between the years 2010 to 2020, this search was carried out during the second semester of 2020. the following descriptors are included, Disciplinary Administrative Process, PAD, Efficiency in Public Administration, Efficiency in the Disciplinary Administrative Process, Efficiency and Management Improvement.